Urgensi Badan Hukum Pada Organisasi Kemasyarakatan (Ormas) Berbentuk Perkumpulan (Studi Pokdarwis Desa Kota Kapur, Kecamatan Mendo Barat, Kabupaten Bangka) - Derita Prapti Rahayu; Faisal; A. Cery Kurnia; Winanda Kusuma; Komang Jaka Ferdian (Faculty of Law Hang Tuah University, 2021)
The role of the community is very strong and cares about the cultural heritage in their area in the form of the Kotakapur site. Communities who are members of POKDARWIS Bekawan, Kotakapur vilage, trying to make a historical tourism village are not easy, it requires the participation of the Regency Government and related agencies in overcoming one by one the problems that become obstacles to the construction of the site. The problem in this writing is what is the scope of Pokdarwis as a community organization? and secondly how is the urgency of legal entities in community organizations in the form of associations?. Problems will be analyzed using normative research methods, by producing answers, namely first, Pokdarwis is a social organization in the form of associations, second, the urgency of legal entities in Pokdarwis is their legal position as legal subjects.